A gender perspective on pest and disease management from the cases of roots, tubers and bananas in Asia and Sub-Saharan Africa - Kawarazuka, Nozomi; Damtew, Elias; Mayanja, Sarah; Sikhu Okonya, Joshua; Rietveld, Anne M.; Slavchevska, Vanya; Teeken, Béla (Frontiers Media, 2020)
Considering gender in research on pests and diseases is increasingly important as it facilitates development of more efficient approaches to increasing the adoption of crop protection technologies and practices by women and men farmers according to their roles, knowledge, and capacities. However, this task is often assigned to social scientists in isolation from agronomists. Meanwhile, agronomists often struggle to understand how taking a gender perspective could enrich their research. Drawing on a number of different cases from both published and unpublished field research in Asia and sub-Saharan Africa, this perspective article illustrates how a gender perspective can broaden the aspects of agronomy research and thereby contribute to improving crop production and scaling up of existing technologies and practices. Its targeted audience are agronomists and development practitioners, in particular, young researchers who are central to transdisciplinary agricultural research in the future.